A Review of Steven Shavell's Foundations of Economic Analysis of Law - Posner, Richard A (Journal of Economic Literature, 2006)
Steven Shavell's Foundations of Economic Analysis of Law (Harvard University Press, 2004) is a major theoretical contribution to “law and economics,” the applied field of economics that studies the economic properties and consequences of legal doctrines and institutions. It is a field of immense practical importance, but unfamiliar to many economists—a situation that Shavell's book bids fair to rectify. This review essay situates Shavell's book in the history of economic scholarship about law and uses the book as a springboard for speculation about new directions in that scholarship.